Geoelectrical Study in Shewasoor Dam Site in Kirkuk/Northern Iraq - Z.Khorshid, Salman; S. AL-Banna, Ahmad; K. Ali, Dahahir (Iraqi Journal of Science, 2023)
A geoelectrical investigation is carried out for a geological consideration in the Shewasoor dam site, which is situated 40 km northeast Kirkuk city. Symmetrical Schlumberger array were applied for fifteen electrical sounding (VES) points, with a maximum spread distance (120-200) meters. Seven vertical electric sounding (VES) points were surveyed in the main valley. Two (VES) points were taken at the area behind the dam, and two other points at the right side of the dam body. Additional four (VES) points measured at the left side within the spillway area. In order to achieve the qualitative and quantitative interpretations manual partial matching technique and (IPI2 WIN) (ID) software are used. The results show that the surface is comprise of recent silt, clay, sand and gravel sediments with trace of water. The subsurface within the valley nearby the dam body is dominanted by claystone underlined by pebbly sandstone with water table condition, while the spillway is characterize by silt and gravel sediments. The area behind the dam body subsurface is composed of silty sandstone underlined by sandy siltstone. It is concluded that the subsurface layers of the dam site are suffering from heterogeneity.